Multimodal communication in building the #BookTok reading community - Sriruttanapaitoon, Penthipa; Karnjanapoomi, Nathaporn; Krongbhumin, Rujsawat; Ingard, Apinya (Journal of Multidisciplinary Academic Research and Development (JMARD), 2026)
This article aims to examine communication practices within the #BookTok reading community on TikTok, which has emerged as a significant cultural phenomenon influencing both the publishing industry and the reading behaviors of younger generations. The study adopts the framework of multimodal communication as its primary analytical approach. The findings reveal that the success of the #BookTok community should not be understood merely as a temporary trend; rather, it is a direct consequence of the effectiveness of multimodal communication. Such communication facilitates two-way interaction, enables easy access to content, supports continuous learning, and systematically connects content of a similar nature. In addition, TikTok’s platform affordances play a crucial role in enhancing these communicative processes, thereby allowing users to convey reading experiences in ways that extend beyond conventional book recommendations or reviews. Consequently, the #BookTok community has come to play a significant role in reshaping reading practices in the context of contemporary digital society. Within this digital reading culture, readers with shared interests are able to connect in virtual spaces to exchange reading experiences, negotiate literary values and meanings, and construct identities at both individual and collective levels.